Ferritin H is a novel marker of early erythroid precursors and macrophages. Issue 6 (24th April 2013) - Wang, Wei; Grier, David D; Woo, Jennifer; Ward, Martha; Sui, Guangchao; Torti, Suzy V; Torti, Frank M; Beaty, Michael W
<x xml:space="preserve">Abstract</x> Aims Macrophages play a critical role in iron homeostasis by recycling iron from red cells and storing it in ferritin, an iron storage protein. The recycled iron is delivered to erythroid precursors for erythropoiesis. In this study, we aimed to determine whether ferritin is highly expressed in macrophages and erythroid precursors, and whether it can be used as a marker for these two cell types. Methods and results A ferritin monoclonal antibody was developed, and immunohistochemistry was performed. In normal bone marrows, ferritin antibody stained early erythroid precursors and macrophages. In contrast, myeloid cells, lymphoid cells and megakaryocytes lacked ferritin expression. In leukaemic bone marrows, ferritin was selectively expressed in erythroid blasts (M6), whereas all other blasts were negative. In lymph nodes, ferritin was highly and specifically expressed in macrophages, whereas lymphocytes completely lacked ferritin expression. In non‐haematopoietic tissues, ferritin antibody highlighted alveolar macrophages in the lung, as well as sinus macrophages in the liver and spleen. Conclusions We conclude that ferritin is a novel and reliable marker for macrophages and early erythroid precursors, and may be of clinical utility in the diagnosis of diseases associated with these two cell types.